MgGa2O4 as a new wide bandgap transparent semiconducting oxide: growth and properties of bulk single crystals. Issue 7 (29th January 2015) - Galazka, Zbigniew; Klimm, Detlef; Irmscher, Klaus; Uecker, Reinhard; Pietsch, Mike; Bertram, Rainer; Naumann, Martin; Albrecht, Martin; Kwasniewski, Albert; Schewski, Robert; Bickermann, Matthias
<x xml:space="preserve">Abstract</x> Bulk MgGa2O4 single crystals with inverse spinel structure were grown from the melt by different methods. The degree of inversion could be changed by suitable annealing, which was confirmed by differential scanning calorimetry analysis and corresponding changes of the specific heat capacity. MgGa2O4 is thermally much more stable at high temperatures than β‐Ga2O3 despite of a higher melting point of about 1930 °C and could be grown under a neutral atmosphere. Melt‐grown MgGa2O4 crystals were found to be either electrical insulators or n‐type semiconductors depending on the presence of oxygen in the growth atmosphere and the growth method applied. Growing the crystals in the presence of oxygen resulted in electrically insulating crystals. For as‐grown and intentionally undoped semiconducting crystals, the free electron concentration was in the range of 1017–1018 cm−3, but the electron mobility was relatively low, just a few cm2V−1s−1. The free electron concentration remained at a level of 1018 cm−3 after annealing in a hydrogen‐containing atmosphere at 600–900 °C for 10 h. On the other hand, annealing in an oxygen‐containing atmosphere above 600 °C for 10–40 h turns the crystals from the semiconducting to the insulating state. The optical bandgap at room temperature amounts to about 4.9 eV. It decreases with temperature at a rate of 1.35 meV/K. Cathodoluminescence spectra of as‐grown crystals show a dominant band at 362 nm. The melt‐grown crystals have sufficient size and structural quality to be used as substrates for epitaxy.